2009
DOI: 10.1152/ajpregu.90740.2008
|View full text |Cite
|
Sign up to set email alerts
|

Short-term blackcurrant extract consumption modulates exercise-induced oxidative stress and lipopolysaccharide-stimulated inflammatory responses

Abstract: induced oxidative stress is instrumental in achieving the health benefits from regular exercise. Therefore, inappropriate use of fruit-derived products (commonly applied as prophalytic antioxidants) may counteract the positive effects of exercise. Using human exercise and cellular models we found that 1) blackcurrant supplementation suppressed exercise-induced oxidative stress, e.g., plasma carbonyls (0.9 Ϯ 0.1 vs. 0.6 Ϯ 0.1 nmol/mg protein, placebo vs. blackcurrant), and 2) preincubation of THP-1 cells with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 52 publications
(69 reference statements)
2
119
0
2
Order By: Relevance
“…Long-term dietary supplementation with pineapple juice decreased colon inflammation in mice [42], while dried plum was able to reduce atherosclerotic lesion in apolipoprotein E-deficient mice [43]. Bromelain, contained in pineapple [44] and anthocyanin [45] contained in blackcurrant have also been shown to inhibit TNF-and IL-6 secretion in vitro. Moreover, polyphenols have been shown to inhibit the LPS-induced TNF-production by microglia [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term dietary supplementation with pineapple juice decreased colon inflammation in mice [42], while dried plum was able to reduce atherosclerotic lesion in apolipoprotein E-deficient mice [43]. Bromelain, contained in pineapple [44] and anthocyanin [45] contained in blackcurrant have also been shown to inhibit TNF-and IL-6 secretion in vitro. Moreover, polyphenols have been shown to inhibit the LPS-induced TNF-production by microglia [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Fruit polyphenols (PPs) and dietary fibres (DFs), including those from apples, kiwifruits and berries, have demonstrated healthpromoting properties and play a key role in health enhancement and disease prevention (Boyer & Liu, 2004;Lyall et al, 2009;Pelucchi et al, 2004;Philpott, Mackay, Ferguson, Forbes, & Skinner, 2007). Thus, it is of considerable interest to explore the possibility of incorporating these fruit bioactives into bread, which is a staple and convenient food consumed throughout the world (Brennan & Cleary, 2007;Sivam, Sun-Waterhouse, Quek, & Perera, 2010;Sivam, Sun-Waterhouse, Waterhouse, Quek, & Perera, 2011;).…”
Section: Introductionmentioning
confidence: 99%
“…In two studies, when a high-phenolic-content antioxidant beverage (Morillas-Ruiz et al, 2005) or a polyphenol-containing sports drink (Morillas-Ruiz, Villegas Garcia, Lopez, Vidal-Guevara, & Zafrilla, 2006) was consumed shortly before 15 min of submaximal aerobic exercise, the magnitude of exercise-induced oxidative stress was significantly reduced. Furthermore, short-term consumption of black currant extract, abundant in polyphenols, reduced exercise-induced oxidative stress and inflammatory responses (lipopolysaccharide inflamma-tory responses) to 30 min of rowing (Lyall et al, 2009), and green tea extract consumed acutely has been shown to stimulate lipid catabolism and increase fat oxidation after 30 min of cycling (Venables, Hulston, Cox, & Jeukendrup, 2008). More recently, 7 days supplementation with quercetin, a natural polyphenol flavonoid, was reported to increase endurance capacity in untrained participants, possibly via increased mitochondrial biogenesis (Davis et al, 2010).…”
mentioning
confidence: 99%